Precision-cut liver slices as an ex vivo model to assess impaired hepatic glucose production - Ligia Akemi Kiyuna; Kishore Alagere Krishnamurthy; Esther B. Homan; Miriam Langelaar-Makkinje; Albert Gerding; Trijnie Bos; Dorenda Oosterhuis; Ruben J. Overduin; Andrea B. Schreuder; Vincent E. de Meijer; Peter Olinga; Terry G. J. Derks; et al. (Communications Biology)
Abstract Fasting hypoglycemia is a severe and incompletely understood symptom of various inborn errors of metabolism (IEM). Precision-cut liver slices (PCLS) represent a promising model for studying glucose production ex vivo. This study quantified the net glucose production of human and murine PCLS in the presence of different gluconeogenic precursors. Dihydroxyacetone-supplemented slices from the fed mice yielded the highest rate, further stimulated by forskolin and dibutyryl-cAMP. Moreover, using 13C isotope tracing, we assessed the contribution of glycogenolysis and gluconeogenesis to net glucose production over time. Pharmacological inhibition of the glucose 6-phosphate transporter SLC37A4 markedly reduced net glucose production and increased lactate secretion and glycogen storage, while glucose production was completely abolished in PCLS from glycogen storage disease type Ia and Ib patients. In conclusion, this study identifies PCLS as an effective ex vivo model to study hepatic glucose production and opens opportunities for its future application in IEM research and beyond.